2020
DOI: 10.3390/nu12092883
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Abdominal Fat Phenotypes and Insulin Resistance in Non-Obese Individuals after Acute Pancreatitis

Abstract: Both type 2 prediabetes/diabetes (T2DM) and new-onset prediabetes/diabetes after acute pancreatitis (NODAP) are characterized by impaired tissue sensitivity to insulin action. Although the outcomes of NODAP and T2DM are different, it is unknown whether drivers of insulin resistance are different in the two types of diabetes. This study aimed to investigate the associations between abdominal fat phenotypes and indices of insulin sensitivity in non-obese individuals with NODAP, T2DM, and healthy controls. Indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…Consistent with this, it has been reported that obesity increases the risk of IR development in patients with AP (58). Furthermore, in non-obese AP patients, increased intra-pancreatic fat deposition was associated with an increased HOMA-IR (homeostasis model assessment-IR) index (59). Among the inflammatory mediators, the adipocytokine IL-6 has been shown to be associated with elevated levels of chronic hyperglycaemia and IR after AP (60).…”
Section: Post-acute Pancreatitis Diabetes Mellitussupporting
confidence: 62%
“…Consistent with this, it has been reported that obesity increases the risk of IR development in patients with AP (58). Furthermore, in non-obese AP patients, increased intra-pancreatic fat deposition was associated with an increased HOMA-IR (homeostasis model assessment-IR) index (59). Among the inflammatory mediators, the adipocytokine IL-6 has been shown to be associated with elevated levels of chronic hyperglycaemia and IR after AP (60).…”
Section: Post-acute Pancreatitis Diabetes Mellitussupporting
confidence: 62%
“…AP is very common, has a considerably high mortality rate and can cause systemic complications (3). The mortality rate of AP has increased from 15 to 30% (4), while the combination of AP with sepsis increases the mortality rate to >50% (5). Although significant efforts have been made to prevent and treat AP (6), no specific treatment methods are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed a significant inverse association between leptin and intra-pancreatic fat deposition (determined with the use of magnetic resonance imaging), independent of abdominal fat distribution in individuals after an attack of acute pancreatitis [65]. Taking into account that individuals after an attack of pancreatitis have significantly higher intra-pancreatic fat deposition compared with healthy controls [66] and given the findings of significant inverse associations of intra-pancreatic fat deposition and indices of insulin sensitivity in non-obese NODAP individuals (but not in T2DM) [67], leptin could be a potential driver of glucose metabolism abnormalities in NODAP. Second, it is thought that leptin may share similar appetite regulating pathways with oxyntomodulin-a gut peptide that whose circulating levels are lower in individuals with NODAP [68].…”
Section: Discussionmentioning
confidence: 99%